KONTRIBUSI SEKTOR JASA PENDIDIKAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI KABUPATEN BERAU: KONTRIBUSI SEKTOR JASA PENDIDIKAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI KABUPATEN BERAU - Nahwani Fadelan (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2022)
The purpose of this research is to determine the contribution of the education service sector to the gross regional domestic product in Berau Regency, so that it can assist the Berau Regency government ini making programs and policies in the future. In this study using secondary data or publication data obtained from the Central Bureau of statistics of Berau Regency using data analysis, namely contribution analysis. With data for the 2015-2019 period of Berau Regency. The result of the study show that the contribution of the Education Services Sector to Gross Regional Domestic Product in 2018 shows a higher contribution value than the 2015-period. This is due to changes in the number of school student and other coasts that change every year.